Friday

April 18, 2014

April 18, 2014

Posted by **Anonymous** on Wednesday, January 9, 2013 at 2:50am.

3p (x=2) = 2p (x=1).

Find

1. p (x=0)

2. p (x-3)

Given e^(-4/3)=0.264

- maths -
**Anonymous**, Wednesday, January 9, 2013 at 6:43amplse solve my sum

**Related Questions**

maths - If x is a Poisson variate such that 3p (x=2) = 2p (x=1). Find 1. p (x=0...

maths - If x is a Poisson variate such that 3p (x=2) = 2p (x=1). Find 1. p (x=0...

algebra: please check - p/3-3p/8=3 p-3p/8=9 p-3p=72 -316 I am not sure if I did ...

Binomial and Poisson distribution - A machine produces ribbon in which flaws ...

algebra - if (2 -q) is one factor of 4 - 2q - 6p + 3pq, what is the other factor...

alegbra - If (2 -q) is one factor of 4 - 2q - 6p + 3pq, what is the other factor...

Chemistry - In which orbital does an electron in a phosphorus atom experience ...

math - statistics - Football team makes in average 2 touchdowns per game. Use ...

maths - Is this right, and where do i go from here??? solve p-1/2-p-2/3=1 (3p-3...

Math ? - If p is a positive integer and is greater than 3. How many prime ...